2011
DOI: 10.1161/strokeaha.110.596502
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging and Gait in Elderly Persons With Cerebral Small Vessel Disease

Abstract: Background and Purpose-Although cerebral small vessel disease, including white matter lesions (WML) and lacunar infarcts, is associated with gait disturbances, not all individuals with small vessel disease have these disturbances. Identical-appearing WML on MRI could reflect different degrees of microstructural integrity. Moreover, conventional MRI does not assess the integrity of normal-appearing white matter (NAWM). We therefore investigated the relation between white matter integrity assessed by diffusion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 38 publications
4
64
0
Order By: Relevance
“…Analyses for each cognitive domain showed the strongest relationship between (1) cingulum bundle microstructural integrity and verbal memory performance and (2) frontal WM and psychomotor speed. 8 However, in the same cohort, the main predictors for the development of incident dementia at 5 years were WM and hippocampal volumes, 34 whereas baseline WM integrity was not associated with decline in cognitive performances 35 In the Vascular Mild Cognitive Impairment Tuscany study, WM microstructural damage was more strongly reflected in Montreal cognitive assessment than mini mental status examination performances, 36 possibly for the presence in Montreal cognitive assessment of items reflecting executive functions and psychomotor speed.…”
Section: June 2016mentioning
confidence: 92%
“…Analyses for each cognitive domain showed the strongest relationship between (1) cingulum bundle microstructural integrity and verbal memory performance and (2) frontal WM and psychomotor speed. 8 However, in the same cohort, the main predictors for the development of incident dementia at 5 years were WM and hippocampal volumes, 34 whereas baseline WM integrity was not associated with decline in cognitive performances 35 In the Vascular Mild Cognitive Impairment Tuscany study, WM microstructural damage was more strongly reflected in Montreal cognitive assessment than mini mental status examination performances, 36 possibly for the presence in Montreal cognitive assessment of items reflecting executive functions and psychomotor speed.…”
Section: June 2016mentioning
confidence: 92%
“…While initial DTI studies show that the disruption of WM microstructure is associated with variable and slow walking in patients with Parkinson’s disease, small vessel disease, and leukoaraiosis (Della Nave et al, 2007, de Laat et al, 2011a, de Laat et al, 2011b, Vercruysse et al, 2015), less is known about normal aging. Since subclinical age-related ischemic changes may contribute to the development of variable and slow walking, this issue is important to the field.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneer DTI studies have identified specific regions of WM microstructure that are associated with variable and slow walking, particularly in patient populations (Della Nave et al, 2007, Bhadelia et al, 2009, de Laat et al, 2011a, de Laat et al, 2011b, Bruijn et al, 2014, Vercruysse et al, 2015). Regions of interest that can potentially affect walking extend beyond those directly linking the motor cortex.…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 4.6b, the dimension of mode-3 is fixed to be 20, and we can see that MDA gets the best result within dimensions of [15,15,20], which indicates the best subspace dimension of mode-1,2. MDA performs better than DATER, which means the mode-3 correlation plays an important role in the action silhouette sequence.…”
Section: Msr 3d Action Datasetmentioning
confidence: 97%
“…However, the vectorization process requires a huge amount of memory, and it is also very time consuming. Recently, tensor decomposition analysis (TDA) [1,9,29] has been successfully applied to various high-dimensional recognition related problems, such as action recognition [7,17,20], face recognition [3,8,27], and gait recognition [6,15,28]. TDA represents high-dimensional data as a multi-fold (mode) tensor, c fChengcheng Jia, Wei Pang, and Yun Fu j Springerg, f2015g.…”
Section: Tensor For Action Recognitionmentioning
confidence: 99%